Form and Operation Mode Analysis of a Novel Solar-Driven Cogeneration System with Various Collector Types - Haofei Zhang; Bo Lei; Tao Yu; Zhida Zhao (International Journal of Photoenergy)
In this study, the form and operation modes of a novel solar-driven cogeneration system consisted of various solar collectors (flat plat collectors (FPC), evacuated tube collectors (ETC), and parabolic trough collectors (PTC)) and ORC (organic Rankine cycle) based on building heating load are analyzed. This paper mainly obtains the fitting formula of thermal efficiency of the ORC power generation device and determines the form and operation mode of the cogeneration system. The form is the same, but the operation modes are different for PTC and FPC or ETC. There are six operating modes, respectively, based on the size relationship between the heating load of buildings and the effective heat collection of the solar collector subsystem when the solar collectors are PTC or FPC and ETC.